As contribuições de uma sequência didática elaborada à luz do Modelo Epistemológico de Referência (MER), na construção dos conhecimentos relativos à educação financeira - Ferreira, Vagner Donizeti Tavares (2019)
The main theme of this thesis is Financial Education, whose main objective was to identify elements that could contribute to the development of the teaching and learning of students of a Mathematics Degree Programm in Financial Education, through the process that leads them to perceive, the close relationship that exists between the financial problems (personal or otherwise) and mathematics. To achieve this goal, we work in the light of the Anthropological Theory of the Dicdatic (TAD), identifying the Reason of Being related to the study of the loans and / or finance object finance, and later it was developed the Epistemological Model of Reference (MER), which under our view contemplates the needs, objectives, skills and abilities provided in the documents, parameters and official curricula related to the Brazilian High School. Then from documentary and bibliographic studies of official documents and textbooks, we have developed the Dominant Epistemological Model to, from such information, construct a sequence of three activities, which were elaborated through a Mathematical Modeling and Theory of Didactical Situation (TSD). The activities of the process were applied to nine volunteer students in the third semester of a Mathematics degree program from a private university located in the city of São Paulo, according to the Didactic Engineering methodology. With the construction of the models by students, which were guided only by the teacher / mediator, they realized that by means of mathematical and / or statistical tools, added to the use of technology, students could form mechanisms of analysis, price comparison and planning, interpreting in a critical way the results obtained, thereby facilitating decision-making in relation to the proposed problems. The context proposed to them was the purchase of a property, but the discussions observed allow us to infer that they understood that this process can be reproduced in several other contexts. We were able to observe that all groups involved were successful in constructing a model from the use of regression and correlation analysis, determination coefficient study, but, mainly, they could identify the need for model corrections according to the needs that emerged from the research carried out to collect the data used by the students. There were difficulties arising from lack or little mathematical knowledge but were healed by the teacher / mediator throughout local institutionalization. We believe that the results disclosed here, have brought a breakthrough in the teaching and learning for loans and / or financing in Financial Education, however, we would like to emphasize that the proposals presented here are not unique and we believe that there are other aspects that must be studied in the light of other theories and methods, always fostering a quality and meaningful education for our students